The Influence of Facilities and Motivation on Employee Productivity at Kairatu Sub-District Office - Paais, Maartje (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
Productivity is crucial things in determining whether an operating system is functioning well, the efficiency indicator, and the competitiveness of a company. There are several objectives of this research, such as (1) to find out the influence of facilities on employee work productivity at the Kairatu Sub-District Office, West Seram; (2) to determine the influence of motivation on employee work productivity at the Kairatu Sub-District Office, West Seram; and (3) to find out more about the influence of facilities and motivation on employee work productivity at the Kairatu Sub-District Office, West Seram. Primary data of this research was obtained by using questionnaires to several selected respondents and conducting interviews. Meanwhile, secondary data obtained from related literatures. The analytical tool used is descriptive analysis of simple linear regression. Therefore, the research findings indicated that there is a partial influence between facilities on employee work productivity at Kairatu sub-district office, West Seram; there is a partial influence between motivation on employee work productivity at Kairatu sub-district office, West Seram; there is a significant influence on facilities and work motivation simultaneously that also affects employee productivity; and there is about 80.9% of the influence of facilities and motivation on employee productivity at Kairatu sub-district office, West Seram and the rest of 19.1% is a percentage influenced by other factors not studied by the researcher.